Immune System Alterations by Aldosterone During Hypertension: From Clinical Observations to Genomic and Non-Genomic Mechanisms Leading to Vascular Damage - Munoz-Durango, N.; Barake, M.F.; Letelier, N.A.; Campino, C.; Fardella, C.E.; Kalergis, A.M. (Current Molecular Medicine, 2013)
Hypertension is traditionally considered a disease in which elevated blood pressure contributes to inflammation and activation of the immune system, leading to cardiovascular injury and end-organ damage. Here, we discuss the effects of aldosterone on the immune system and aldosterone’s contribution to vascular pathogenesis. Studies in human have suggested a broader role for aldosterone, beyond elevating blood pressure. Recent clinical data support the notion that aldosterone can directly alter the function of the immune system and cause vascular-damaging inflammation. Clinical observations have been reproduced in experimental models of hypertension, further supporting the idea that an aberrant immune response contributes to the onset of hypertension. Such studies have shown that myeloid cells are required to induce the disease and IL-17-producing CD4+ T cells may contribute to maintaining aldosterone-mediated hypertension. In addition, regulatory T cells diminish the inflammatory damage caused by aldosterone during hypertension. This is a very active area of research that could lead to new therapeutic targets for treating hypertension.
Keywords: Aldosterone